Workshop Activities to Increase Team Cohesiveness at the Department Learning Center (DLC) - Meidiya Ende Repa; Devi Damayanti (Journal of Economics, Business, and Government Challenges, 2023)
Department LC (DLC) is a work unit of PT. GREAT INTEGRATED. DLC functions as an employee training and development facilitator at PT. GREAT INTEGRATED. in DLC there is less than optimal output and there are consumer complaints regarding the quality of the implementation of the training program in the form of conveying information on less than optimal training implementation schedules. Employees also express complaints when working with a team, even when working deadlines. These complaints: the appearance of anxiety, dizziness, and lack of comfort when working in a team. The results of the open system diagnostic method found that the complaint was caused by conflict in interaction between teams, which was caused by limited non-formal communication, such a situation resulted in the intensity of direct interaction between team members being less than optimal. This form of communication causes misunderstanding, the misunderstanding is not because the team is unable to express opinions, so further forms of intervention for DLC are a function of the team itself, because the cohesiveness of the DLC team is not optimal and it is necessary to carry out team building activities to increase team cohesiveness.